(2w+5)(4w-6x-7)=

Simple and best practice solution for (2w+5)(4w-6x-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2w+5)(4w-6x-7)= equation:


Simplifying
(2w + 5)(4w + -6x + -7) = 0

Reorder the terms:
(5 + 2w)(4w + -6x + -7) = 0

Reorder the terms:
(5 + 2w)(-7 + 4w + -6x) = 0

Multiply (5 + 2w) * (-7 + 4w + -6x)
(5(-7 + 4w + -6x) + 2w * (-7 + 4w + -6x)) = 0
((-7 * 5 + 4w * 5 + -6x * 5) + 2w * (-7 + 4w + -6x)) = 0
((-35 + 20w + -30x) + 2w * (-7 + 4w + -6x)) = 0
(-35 + 20w + -30x + (-7 * 2w + 4w * 2w + -6x * 2w)) = 0

Reorder the terms:
(-35 + 20w + -30x + (-14w + -12wx + 8w2)) = 0
(-35 + 20w + -30x + (-14w + -12wx + 8w2)) = 0

Reorder the terms:
(-35 + 20w + -14w + -12wx + 8w2 + -30x) = 0

Combine like terms: 20w + -14w = 6w
(-35 + 6w + -12wx + 8w2 + -30x) = 0

Solving
-35 + 6w + -12wx + 8w2 + -30x = 0

Solving for variable 'w'.

The solution to this equation could not be determined.

See similar equations:

| (7-4i)(5-2i)=0 | | h(x)=x^4+7x^2+7 | | 10-17x+7x^2=0 | | -6x-6y-4x+15y= | | 5t^2+2t-3=0 | | Ln(0.01+1)= | | 13-(-9x)+3x-(-11)= | | 9-2x=9-7x | | 7m^2-28m-224=0 | | 2b-4-9b-9= | | x-0.5x-0.75x-0.5x=200 | | 8/27+1/9+4/9= | | 5x^4*2x^3= | | 0=-4x^2+24x+12 | | 9(n+2)+8n+7= | | .25+.6(50-m)=0 | | 15a^2-3ab-18b^2=0 | | 3x^2+12=66 | | 4v-8=4v-12 | | 1+6y-16y= | | 3x-19x= | | -3y+2=10y+30 | | 2z+.6=3z+.2 | | f(x)=-x^4+x^2 | | 26-2x=10+6x | | 7(18-x)-6(3-5x)=-(7x+9)-3(2x+5) | | 18(x+18)=21squared | | 2x+.6=3z+.2 | | f(x)=5x^3+7x^2-x+9 | | 1x=-1x-8 | | 4x+3-2x=33 | | 2n+5=-n-13 |

Equations solver categories